Balancing Growth and Impact: A Conjoint Analysis of Public Preferences for Data Center Policy - Fengxiu Zhang; Shuping Wang; Saba Siddiki; David W. S. Wong; Jie Xu (Social Science Quarterly, 2026)
Abstract Objective This study examines public preferences for policy provisions governing the siting, construction, and operation of data centers. Method Drawing directly on Virginia's 2024–2025 legislative portfolio on data centers, we employ a conjoint experimental design to examine public preferences for alternative policy provisions on data centers. Data were collected through a 2025 survey of 1004 Virginia residents. Results We find broad public support for regulatory oversight of data centers, but the magnitude of support varies across policy provisions. Respondents show the strongest preferences for policy provisions addressing direct, immediate, and visible issues related to data centers, including undergrounding new transmission lines near homes, restricting data center development in sensitive areas, mandating report of water and energy usage, and requiring public review prior to project approval. Support is comparatively weaker for policy provisions addressing less visible or more technically complex issues, including electricity rate setting and environmental impact assessments. Subgroup analyses further reveal that heterogeneity in policy preferences is associated more strongly with individual characteristics—including education, race, age, and political ideology—than with regional context.